Modeling and simulation of an industrial indirect solar dryer for Iroko wood (Chlorophora excelsa) in a tropical environment - Simo-Tagne, Merlin; Zoulalian, André; Remond, Romain; Rogaume, Yann; Bonoma, Beguidé (Maderas. Ciencia y Tecnología, 2017)
This paper presents a modeling of an instrumental indirect solar wood dryer less expensive functioning in a Cameroonian climate applied to the climate of Yaoundé. The dryer is easy to build and electric energy is only used for the fan. Applications are done on Iroko wood (Chlorophora excelsa), a tropical wood 50mm thick most utilized in Africa. A satisfactory agreement between experimental and numerical results was found. Influences of thickness, wood initial water content and airflow rate were studied.